Bloodstream Infections in a Nepalese Tertiary Hospital-Aetiology, Drug Resistance and Clinical Outcome - Siwakoti, Shraddha; Sah, Rinku; Chhetri, Roshan; Khanal, Basudha (Journal of Nepal Health Research Council, 2024)
Background: Bloodstream infections (BSIs) are a leading cause of sepsis-related morbidity and mortality globally. We present the pathogenic agents of bloodstream infections, their antimicrobial susceptibilities, and associated outcomes, with a focus on drug-resistant cases. Methods: We included all adult patients admitted to B.P. Koirala Institute of Health Sciences with blood culture-positive sepsis from July 2019 to June 2020. Blood cultures and antimicrobial susceptibility tests followed standard methods. Demographic, clinical, and microbiological data, including clinical outcomes, were documented. Patients were categorized into non-multidrug resistant (non-MDR), multidrug resistant (MDR), and extensively drug resistant (XDR) groups for analysis of clinical outcomes. Results: Of 5372 adult patients with suspected bloodstream infections, 475 (9%) had culture-positive infections with 536 organisms cultured. The median age of the patients was 42 (25-60) years, and 47% of the patients were women. There were 146 (31%) non-MDR, 220 (46%) MDR and 109 (23%) XDR cases. Common pathogens were Staphylococcus aureus (27%), Acinetobacter spp (20%), and Klebsiella spp (15%). The overall in-hospital mortality rate was 8% (38/475). Mortality was highest among XDR patients (53%), compared to MDR (29%) and non-MDR patients (18%) (p < 0.001). Patients in XDR group had longer hospital stays compared to MDR-BSI and non-MDR BSI patients (p=<0.001). After adjusting for risk factors, the odds ratio for in-hospital mortality in XDR patients was 2.52 (CI 1.11–5.72, p = 0.02). Conclusions: Drug-resistant pathogens are prevalent in our setting, causing bloodstream infection. Extensively drug-resistant bacteria in the blood are independently and significantly linked to increased mortality. Keywords: Bloodstream infections; clinical outcome; drug resistance.